Cooperation among co-basin countries - key to effective management of the Ganges water resources - Khan, Tauhidul Anwar, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 1998)
The Ganges is an international river with its basin encompassing parts of India, China, Nepal and Bangladesh. The flows of the Ganges are highly seasonal and heavily influenced by the monsoon rainfall. More than 80% of the total rainfall over the basin occur during only four monsoon months from June to September. Seasonal overabundance and scarcity of water are the two perennial impediments which have been frustrating the overall development efforts in the Ganges basin area. The area constituting the Ganges basin is one of the poorest in the world despite its rich natural endowments of land, water and people. The fate of the entire basin could have been changed dramatically through meaningful and effective cooperation amongst all the co-basin countries by harnessing, development and management of the water resources of this river. The desired development of this common resource however remained neglected. Basinwide development and management of water resources should be the major option for future development of the Ganges area. Conservation of waters would no doubt be the primary means for tackling the huge problems of alternative flooding and water scarcity during wet and dry seasons and meet the expanding water and power needs for sustaining a rapidly growing economy and population. Firm political commitment from the Governments of India, Nepal and Bangladesh for meaningful cooperation would be the essential prerequisite to launch a programme for effective development and management of water resources of the Ganges. A congenial atmosphere in the relations amongst the three countries shall therefore be crucial. With signing of the Ganges Water Sharing Treaty between India and Bangladesh in 1996 and the Mahakali Treaty between India and Nepal, a new climate of trust and confidence in the region has emerged. All concerned may, therefore, take advantage of this new climate. In the interest of all, the political and conceptual problems now need to be more purposefully addressed especially as the underlying commonality of interests in the Ganges is overwhelming.
USCID conference on shared rivers
Ganges water resources
Not digitized by CSUL Digital Services.
Presented at River basin management to meet competing needs: proceedings from the USCID conference on shared rivers held on October 21-31, 1998 in Park City, Utah.